EnglishTeachers’ Professional Development During COVID-19: Indonesian Elementary English Teacher Context - Latifah Fatmawati; Dewi Rochsantiningsih; Slamet Supriyadi (AL-ISHLAH: Jurnal Pendidikan, 2022)
Teachers have important role in learning process to improve the quality of education output and outcome Indonesia. Therefore, to be professional teachers, activities should be carried out during COVID-19 pandemic to develop professionalism of teachers. The purpose of this research is to discover what teacher professional development (TPD) activities that the teachers could engage during COVID-19 pandemic. This study also examines the viewpoints of teachers from both private and public schools. The method of the research employs qualitative research and focuses on case study technique utilized to investigate teachers’ thoughts on what TPD activities they participated in during the COVID-19 pandemic. The result of the research indicates that elementary teachers can still participate in TPD activities using the existing online platform even during pandemic. Teachers can develop their professionalism in creating and developing online media in learning during COVID-19 pandemic. In conclusion, the COVID-19 pandemic provides new TPD opportunities for teachers and expands their understanding of internet technology and promote collaboration among teachers. However, further research should be conducted to address teachers' professional development in a deeper and broader perspective in Indonesia. It is expected to cover wider areas of teachers from different institution including higher education institutions. In order that we can learn about the types of TPD activities that may be done remotely during the pandemic from many perspectives.